2023
DOI: 10.1590/1519-6984.264249
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of factors influencing bacterial leaf blight in rice production

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial leaf blight that is a major threat to rice production. Crop losses in extreme situations can reach up to75%, and millions of hectares of rice are affected each year. Management of the disease required information about the spatial distribution of BLB incidence, severity, and prevalence. In this study, major rice-growing areas of Pakistan were surveyed during 2018-2019 for disease occurrence, and thematic maps were developed using geographic information syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Location of the sample is believed to reflect valuable information due to the apparent spatial correlation quantifiable in terms of separation distance and direction. Samples taken close together are expected to be more alike than samples far apart [9,10] The spatio-temporal distribution of grain discoloration incidence in Kharif 2012 and 2013 varied with districts, the highest was in Bellary district (33.82% and 31.24%) and lowest was in Chikamagalur district (17.54% and 19.53%) which comes under Hilly area which comes under irrigated maidan area of North-Karnataka. Mathew Baite et al [11] reported the grain discolouration of rice in Cuttak , where the overall incidence of the disease ranged from 25 to 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Location of the sample is believed to reflect valuable information due to the apparent spatial correlation quantifiable in terms of separation distance and direction. Samples taken close together are expected to be more alike than samples far apart [9,10] The spatio-temporal distribution of grain discoloration incidence in Kharif 2012 and 2013 varied with districts, the highest was in Bellary district (33.82% and 31.24%) and lowest was in Chikamagalur district (17.54% and 19.53%) which comes under Hilly area which comes under irrigated maidan area of North-Karnataka. Mathew Baite et al [11] reported the grain discolouration of rice in Cuttak , where the overall incidence of the disease ranged from 25 to 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections can result in crop bacterial diseases. Common diseases include leaf blight, canker, bacterial wilt and soft rot 1–6 . The associated pathogenic bacteria not only extract nutrients and water from the host crops, but also disrupt the normal physiological activities of the host, leading to various agricultural diseases 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to grain yield, improving grain quality is also important for rice breeders (Cordero-Lara, 2020;Tong et al, 2019;Custodio et al, 2019;Nair, 2019;Kamrul et al, 2020). The main areas of rice sowing in the world are used for growing white-grained varieties (Ahmad et al, 2023;Javed et al, 2022). Wild-growing ancestors of cultivated rice had a colored grain pericarp.…”
Section: Introductionmentioning
confidence: 99%